Energy-input analysis of the life-cycle of microalgal cultivation systems and best scenario for oil-rich biomass production. (15th September 2015) - Abu-Ghosh, Said; Fixler, Dror; Dubinsky, Zvy; Iluz, David
Graphical abstract: Highlights: Aim: To realize the energy inputs of the LCA to produce oil-rich algal biomass for biodiesel. We considered recent technologies and main bottlenecks in algal biomass production. We calculated and compared the energy requirements of the algal cultivation systems. Lowest energy input for a complete harvesting process requires ∼4 MJ per m −3 algal suspension. We propose the best scenario to grow microalgae for biodiesel. Abstract: An energy-input analysis of the life-cycle of microalgal cultivation systems was performed to study the oil-rich biomass production from fast-growing microalgae, for biodiesel production purposes. We estimated and compared the energy demands for the algal biomass cultivation in open-ponds (OP) with that required in closed-system photobioreactors (PBR) based on the new technologies. We also present the best microalgal candidates that show the highest biomass productivity and lipid yield indoors (laboratory scale), and discuss their potential to be used for full-scale biodiesel production. The results show that the energy requirements are highly dependent on the final mass concentration and/or using industrial wastes, with PBR cultivation being the largest energy consumer. Our offered scenario to minimize energy inputs and to increase algal-oil yields considers the most ideal cases, which could be the most promising model for energy-efficient biofuel production. Although biodiesel production by any of these systems is still not economically competitive with fossil fuel, recent suggestions on how to increase the efficiency of both systems are discussed, based on our energy-input assessment, with a critical evaluation of all stages for large-scale production of oil-rich microalgal biomass.